Production of (other) times and spaces in the processes of compulsory schooling of young people in public secondary schools in Córdoba (Itinerarios Educativos, 2025)
In this article we present some results of two research studies that set out to study secondary education and its schooling processes, focusing on school formats and two of its structural components, space and time, and their articulation with the construction of schooling conditions to guarantee the right to compulsory education. In these investigations, we start from the assumption that the spatial and temporal dimensions are key in the configuration and organization of the school system, so we proposed to study them in the framework of the expansion of the right to secondary education.We propose some conceptualizations on space and time that we have been discussing and coining (Castro and Martino, 2021) which allow us to analyze some fragments of the fieldwork carried out in two schools in the city of Córdoba, around more heterogeneous and mobile ways of being of bodies, with more diverse temporalities and spatialities, exchanges and interactions that surpass the spatio–temporal structures instituted in the framework of a provincial policy that intervenes on absenteeism, on the one hand, and of an institutional pedagogical project intertwined with the community of belonging, on the other.
Keywords: School time; school space; schooling conditions; secondary school